2015
DOI: 10.1073/pnas.1420855112
|View full text |Cite
|
Sign up to set email alerts
|

Antisense long noncoding RNAs regulate var gene activation in the malaria parasite Plasmodium falciparum

Abstract: The virulence of Plasmodium falciparum, the causative agent of the deadliest form of human malaria, is attributed to its ability to evade human immunity through antigenic variation. These parasites alternate between expression of variable antigens, encoded by members of a multicopy gene family named var. Immune evasion through antigenic variation depends on tight regulation of var gene expression, ensuring that only a single var gene is expressed at a time while the rest of the family is maintained transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 48 publications
10
142
1
1
Order By: Relevance
“…Greater knowledge of the role of epigenetic modifications could improve understanding of the cardiac fibrosis pathogenesis [25]. Furthermore, some studies continue to find novel pathways, including the important role of LncRNA transcripts in epigenetic gene regulation [26]. LncRNA regulates numerous physiological and pathological processes, including cell proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Greater knowledge of the role of epigenetic modifications could improve understanding of the cardiac fibrosis pathogenesis [25]. Furthermore, some studies continue to find novel pathways, including the important role of LncRNA transcripts in epigenetic gene regulation [26]. LncRNA regulates numerous physiological and pathological processes, including cell proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…They frequently act as lynchpins for epigenetic regulators targeting non-specific enzymes to specific sites within the genome. Also, in P. falciparum ncRNAs have been associated with regulation of virulence genes (31,32). Various ncRNA transcripts have been detected by different methods (3337).…”
Section: Introductionmentioning
confidence: 99%
“…The function of the sense transcript produced from the intron of var genes remains elusive. The natural antisense RNA remains associated with chromatin and its transcription has been correlated with var gene activity (21,31,42). However, it is not yet clear whether this antisense RNA is cause or consequence of transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms regulating this on-off switching have not yet been elucidated completely, but it is known that it is a highly organized process that mainly relies on epigenetic processes including post-translational histone modifications and differential sub-nuclear localization (Scherf, Lopez-Rubio and Riviere 2008;Volz et al 2012;Jiang et al 2013). Recently, it was found that antisense long non-coding RNAs (lncRNAs) initiating from var introns are incorporated into chromatin, and that expression of these antisense lncRNAs in trans triggers activation of a silent var gene (Amit-Avraham et al 2015). Also the expression of specific var gene subgroups is tightly regulated, as PfRNase II, a chromatin-associated exoribonuclease, mediates the degradation of nascent RNA and controls the silencing of group A var genes implicated in the pathogenesis of CM (Zhang et al 2014).…”
Section: Antigen Variation and Antigen Diversitymentioning
confidence: 99%